Review on a Digital Library Websites of Universities - Bhattacharjya, Sumanta (Journal of Advanced Research in Library and Information Science, 2022)
The reading and borrowing facilities are available to all the employees of Santiniketan Medical College of West Bengal. Books may be borrowed by submitting the Requisition Form to the Librarian. For others, only reading at the Library reading Hall, is available with prior permission/recommendation from the competent authority. Every user has to submit an Application Form containing the detailed particulars to the Librarian. Research scholars and readers associated with different universities of India and abroad are frequent users of this library. This library owns many valuable books, documents and gazettes which are not available in other libraries of this country, including the National Library. How to cite this article: Bhattacharjya S. Review on a Digital Library Websites of Universities. J Adv Res Lib Inform Sci 2022; 9(1): 28-30.